História da saúde pública no Estado de São Paulo History of Public Health in the S. Paulo State, Brazil - Rodolfo dos Santos Mascarenhas (Universidade de São Paulo, 1973)
Estuda-se a história, através da evolução dos serviços estaduais de saúde pública em São Paulo, desde 1891 até o presente. Dois vultos se destacam: Emílio Ribas e Geraldo de Paula Souza. Emílio Ribas conseguiu debelar no fim do século passado surtos epidêmicos de febre amarela, febre tifóide, varíola e cólera e, na Capital, malária. Prova, em um grupo de voluntários, no qual foi o primeiro, a transmissão, por vector, de febre amarela, repetindo, um ano depois, a experiência norte-americana em Cuba. Funda o Instituto Butantã, entregando-o a outro cientista, Vital Brasil. Paula Souza reorganiza, em 1925, o Serviço Sanitário do Estado, introduzindo o centro de saúde, a educação sanitária, a visitação domiciliaria. Lidera, posteriormente, no SESI, a assistência médica, odontológica, alimentar e social do operário. Em junho de 1947 foi criada a Secretaria da Saúde Pública e da Assistência Social cujo primeiro titular foi o Dr. José Q. Guimarães. Deu-se ênfase à implantação de campanhas de erradicação ou controle de doenças transmissíveis (malária, chagas, poliomielite, variola, etc.) e à reforma total da Secretaria da Saúde iniciada em 1970. The history through the evolution of the estate public health services in S. Paulo from 1891 till 1971 was studied. Two public health leaders are distinguished: Emilio Ribas and Geraldo de Paula Souza. At the end of the later century Emilio Ribas succeeded in overcoming outbreaks of epidemics, such as yellow fever, smallpox, cholera and malaria in the city of S. Paulo. In a group of volunteers he experimented the transmission of yellow fever by vector, and one year after the American experience in Cuba. He set up the Institute Butantã and placed it in the hands of another great scientist, Vital Brasil. In 1925 Paula Souza reorganizes the Sanitary Service of the State, introducing the health center, public health education, home visits and so on. Later, in the SESI (Serviço Social da Indústria), he leads the medical, dental, nutritions and social care of the worker. The S. Paulo State - Department of Health and Social Welfare - was created in July 1947 and its first title-holder was José Queiroz Guimarães, Doctor. It was given emphasis to the implementation of eradication campaigns or transmissible diseases control (malaria, barber, poliomyelitis, smallpox and so on) and to the total reorganization of the S. Paulo State Department of Health and Social Welfare started in 1970.